(untitled) (International journal of artificial intelligence, 2026)
This article analyzes the theoretical and practical aspects of higher education terminology from a linguistic perspective. The study examines the essence of the concepts of term and terminology, the sources of formation of higher education–related terms, as well as their semantic and functional characteristics. In addition, the presentation of higher education terms in explanatory, terminological, encyclopedic, and bilingual or multilingual dictionaries is comparatively analyzed. Differences and similarities in the interpretation of identical terms across various dictionaries are identified, with particular attention paid to issues of semantic precision and normativity. The research findings demonstrate the necessity of ensuring inter-dictionary consistency of higher education terminology, systematically regulating the balance between national and international terms, and strengthening terminological norms. The article has scientific and practical significance for the study of higher education terminology, lexicographic practice, and the effective use of terms.